A digital atlas for the Byzantine and Post Byzantine Churches of Troodos region (central Cyprus) - Agapiou, Athos; Georgopoulos, Andreas; Ioannidis, Charalabos; Ioannides, Marinos (My University, 2010)
This paper presents the results produced during an interstate research project between universities of Greece and Cyprus using Web technologies. The main aim of the Digital Atlas is to create a unique product for the visualization of the cultural heritage of Cyprus, while at the same time to be able to provide information to the end-users. The region of Mountain Troodos is characterized by one of the largest groups of churches and monasteries of the former Byzantine Empire. The complex of 10 monuments – churches, which are all richly decorated with murals, provides an overview of Byzantine and post-Byzantine painting (frescoes religious paintings) on Cyprus. These churches – monuments where inscribed to the UNESCO list of World Heritage Monuments and attract a large number of tourists every year (over 1 million). The above application consists of a WebGIS tool, using the ArcGIS Server software. The WebGIS includes a detail 3D reconstruction of the surrounding area of the monuments using grayscale high resolution orthophotos and 3D digital “light” models of the monuments, produced in Google SketchUp software, using non-rigorous topometric methods. Moreover the application includes no-spatial information about the monuments, such as relevant bibliography, photos of the interior and exterior of the monuments and also audiovisual data. Finally this digital tool provides to the end-users a brief, time-stamped, historical background information about the Byzantine and postByzantine monuments.
Keywords: WebGIS; 3D model; Cultural Heritage; Digital Atlas